Quantitative analysis of organic acids in aqueous extracts of Tamarindus Indica pulp and preparation of tamarind powders - Wirod Chaipornpokin (Chulalongkorn University, 2012)
Thesis (M.Sc.)--Chulalongkorn University, 2008